Creation and evaluation of a gender diversity focused cultural competency training for phlebotomists: Study protocol for a randomized controlled trial - Henrietta Maku; Christina C. Pierre; Dina N. Greene; E. Henderson; Camille L. Rogers; Cameron Whitley; Gabrielle N. Winston-McPherson (Heliyon)
Background: Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, and Asexual (LGBTQIA+) patients face unique challenges when navigating the healthcare system. In laboratory medicine, LGBTQIA + patients may experience bias and stigma when interacting with phlebotomists and laboratory professionals leading to substandard care and safety concerns. Education and job-specific training can help improve cultural competency on the part of lab staff. Our group developed a web-based LGBTQIA + cultural competency training tailored to the educational needs of phlebotomists with the goal of improving interactions with gender-diverse patients. Methods: We propose a randomized control group study to compare the effectiveness of a gender-cultural competency training to improve phlebotomist knowledge, attitudes, and care delivery skills related to gender-diverse patients. The development and design of the education followed consensus recommendations. In order to appeal to our target audience, the educational material is accessible, engaging, and not- time- or labor-intensive. To distribute the training to several sites over a limited time, we will utilize an online educational platform as opposed to a face-to-face curriculum. Conclusions: The principal investigators anticipate that providing adequate training to phlebotomists will statistically improve their overall cultural competency and lead to an improved ability to provide affirming, safe and competent care to patients within the gender-expansive community. If successful, we anticipate that both national and international organizations can easily adapt this curriculum for their use.